An integrated and smart ASEAN: Overcoming adversities and achieving sustainable and inclusive growth - Cyn-Young Park; Bernard Yeung (Asian Development Bank Institute (ADBI), 2021)
Asia's economic significance has risen substantially over the past several decades. Further economic development in ASEAN, with its massive population, requires very efficient utilization of resources and cross-border cooperation. While ASEAN has much to gain from economic cooperation and integration, it faces non-trivial growth and integration barriers: (i) an infrastructure development gap; (ii) an education gap; and (iii) a market institutions gap, especially in financial sectors, which is very much related to governance issues such as government inefficiency and policy ineffectiveness. The paper offers an overall perspective on maintaining sustainable and inclusive development in ASEAN - the broad trend and the barriers. Three lessons emerge for ASEAN to seize the economic opportunities. First, the governments can gain great mileage in sustainable development from building sound market institutions, catering to financial and economic stability, and establishing sound health care and redistribution programs. Second, governments should promote deeper regional economic integration, invest in digital infrastructure and wireless access, and invest in training workers and companies to tune into the virtual technology. They should partner with the private sector to multiply the gains from the opportunities arising from crises. Finally, governments should embrace digital−IOT−AI technology while considering strategies to address the associated challenges.
Keywords: F00; F02; F15; F5; F63; O1; 330; ASEAN; economic cooperation and integration; the digital-IOT-AI transformation; COVID-19; geopolitical tensions